Plain Jane and the mermaid - Brosgol, Vera (First Second, an imprint of Roaring Brook Press, 2024)
"Jane is incredibly plain. Everyone says so: her parents, the villagers, and her horrible cousin who kicks her out of her own house. Determined to get some semblance of independence, Jane prepares to propose to the princely Peter, who might just say yes to get away from his father. It's a good plan! Or it would've been, if he wasn't kidnapped by a mermaid. With her last shot at happiness lost in the deep blue sea, Jane must venture to the world underwater to rescue her maybe-fiancé. But the depths of the ocean hold beautiful mysteries and dangerous creatures. What good can a plain Jane do?"--